Respuesta :

Answer:

The 4th choice: The graph of the equation has roots at x = -b/a and x = -d/c

Explanation:

If we have an equation of the form

[tex](ax+b)(bx+c)=0[/tex]

then it must be that either

[tex](ax+b)=0[/tex]

or

[tex](bx+c)=0[/tex]

The first equation gives

[tex]\begin{gathered} ax+b=0 \\ x=-\frac{b}{a} \end{gathered}[/tex]

and the second equation gives

[tex]\begin{gathered} cx+d=0 \\ x=-\frac{d}{c} \end{gathered}[/tex]

Hence, the roots of the equation turn out to be

[tex]x=-\frac{b}{a},x=-\frac{d}{c}[/tex]

Therefore, we conclude that the equation of the form (ax + b) (cx + d) tells us about the roots of the function, and hence, choice 4 is correct.

ACCESS MORE